Photoexcited sulfenylation of C(sp3)–H bonds in amides using thiosulfonates. Issue 19 (3rd May 2022) - Bi, Wen-Zhu; Zhang, Wen-Jie; Li, Chen-Yu; Shao, Lu-Hao; Liu, Qing-Pu; Feng, Su-Xiang; Geng, Yang; Chen, Xiao-Lan; Qu, Ling-Bo
Abstract : Photoexcited organic dye-catalyzed synthesis of sulfenyl amides through a direct sulfenylation of C(sp 3 )–H bonds using thiosulfonates as a sulfur source at room temperature. Abstract : A photoexcited sulfenylation of C(sp 3 )–H bonds in amides is developed for the synthesis of sulfenyl amides using thiosulfonates as a sulfur source. In the presence of easily available and inexpensive Na2 -eosin Y, TBHP and K2 CO3, various sulfenyl amides can be obtained under the irradiation of blue light at room temperature.